Incidence of lip malignancies in Germany—data from nine population‐based cancer registries. (2nd March 2017) - Singer, Susanne; Zeissig, Sylke Ruth; Emrich, Katharina; Holleczek, Bernd; Kraywinkel, Klaus; Ressing, Meike
Abstract : Background: The objective of this study was to analyse the incidence of lip malignancies in Germany. Methods: Data from population‐based cancer registries covering a population of 39 million inhabitants from 14 federal states were pooled. Lip malignancies were classified according to the International Classification of Diseases (ICD‐10). Age‐standardised incidence rates and annual percentage changes in the incidence trends of lip cancer (C00), melanoma of the lip (C43.0), and non‐melanoma skin cancer of the lip (C44.0) were calculated. Results: Lip cancer (C00) incidence rate was 0.57/0.15 per 100 000 (men/women) in 2003 and 0.52/0.18 in 2012. In women, the change was statistically significant. Melanoma lip cancer (C43.0) incidence rates both in men and women were 0.02 in 2003 and 0.01 in 2012. Incidence rates of non‐melanoma skin cancer of the lip (C44.0) significantly increased from 1.6 in 2003 to 2.1 in 2012 in men and from 1.5 in 2003 to 2.4 in 2012 in women. In lip cancer (C00), the vast majority (98% in men/93% in women) were squamous cell carcinomas and 2%/7% were basal cell carcinoma. In men, 56% of non‐melanoma skin cancers (C44.0) were squamous cell carcinoma, whereas these were only 27% in women. Conclusions: The incidences of non‐melanoma skin cancer of the lip increased over time in Germany in both sexes. Lip cancer incidence increased in women, while it stayed stable in men. Melanoma of the lip did not change in incidence. The distribution of histology in non‐melanoma skin cancer of the lip differed by sex.